PELUANG PNS PEREMPUAN DALAM MEMPEROLEH JABATAN STRUKTURAL: STUDI KUALITAS KESETARAAN GENDER DI PEMERINTAH KOTA SEMARANG - PUJI ASTUTI, PUJI ASTUTI (Politika: Jurnal Ilmu Politik, 2012)
Abstract The involvement of  women in public area is not a new phenomenon, because for along time women not only do their role in domestic area. But their involvement in public area unequal with their quantity and their opportunity to achieve strategic official like men. In fact, it does not easy for women to achieve strategic position with their capacities. Practical of  politics and government point out that women involvement in thus area just being as a normative assurance. In empirical condition it is too hard for women for being official because of internal factor  like  unconfident with their abilities and skills. Commonly  women also  believe that they do work just assist their husband and develop career is  a second choices. But the dominant factor are  cultural patriachi that influence mindset which is believe that women shouldn’t doing competition with men for getting official.  There  is also political penetration as a constraint  which is women having less opportunity and believe that politics is full of dirty  and it’s not good for women. All of those reasons contribute that gender quality is still hard to be realitation, include in Semarang City, although gender quality is a human right and advancing gender quality is being UN and a global commitment. Keywords : Domestic Area; Gender Quality; Culture Patriachi